2024
DOI: 10.1186/s13005-023-00403-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of AH plus bioceramic sealer, Bio-C Sealer, and ADseal root canal sealer

Tamer M. Hamdy,
Manar M. Galal,
Amira Galal Ismail
et al.

Abstract: Background The aim of this study was to evaluate the physicochemical properties of two newly introduced premixed calcium silicate-based root canal sealers (AH Plus Bioceramic Sealer and Bio-C Sealer) compared to a resin-based root canal sealer (ADseal root canal sealer). Methods Solubility, pH analysis, calcium ion release, and film thickness of each sealer were evaluated following ISO guidelines. The data were examined using the two-way ANOVA test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…New operative techniques have been developed, focusing on making chemomechanical preparation more rapid and efficient, and ideally increasing quality by providing more predictable cleaning and shaping results (7)(8)(9)(10). As a consequence, there has been a similar interest in improving the simplicity and quality of root canal obturation, with a continuous request for alternative sealers that are more biocompatible, more bioactive, and more capable of bonding to the root canal wall when compared to traditional resin-based or eugenol-based sealers (11)(12)(13)(14)(15)(16). Therefore, the criteria for the ideal material for use in endodontic obturations must be comprehensive Physicochemical properties of two commercially available bioceramic sealers: An in vitro study and include the following characteristics: non-toxic, insoluble in tissue fluids, dimensionally stable, antibacterial, hard tissue conductive, biocompatible, radiopaque and easy to handle (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New operative techniques have been developed, focusing on making chemomechanical preparation more rapid and efficient, and ideally increasing quality by providing more predictable cleaning and shaping results (7)(8)(9)(10). As a consequence, there has been a similar interest in improving the simplicity and quality of root canal obturation, with a continuous request for alternative sealers that are more biocompatible, more bioactive, and more capable of bonding to the root canal wall when compared to traditional resin-based or eugenol-based sealers (11)(12)(13)(14)(15)(16). Therefore, the criteria for the ideal material for use in endodontic obturations must be comprehensive Physicochemical properties of two commercially available bioceramic sealers: An in vitro study and include the following characteristics: non-toxic, insoluble in tissue fluids, dimensionally stable, antibacterial, hard tissue conductive, biocompatible, radiopaque and easy to handle (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, the various bioceramic sealers commercially available nowadays show a great diversity in their biological, chemical, and physical properties: most of them are mainly related to their chemical composition, but also to the manufacturing process. Such differences can also significantly affect clinical performance, and consequently, new commercially available products must be carefully investigated to assess quality and check differences with existing products (11)(12)(13). It has been shown that the safety data sheets and manufacturer details of currently available bioceramic sealers were imprecise.…”
Section: Introductionmentioning
confidence: 99%